Pemberdayaan Masyarakat Pulau Wisata Lakkang Melalui Desain Dan Pemanfaatan Bahan Limbah Menjadi Industri Kreatif - Nurul Nadjmi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
Environmental problems have been being one of global issues, after almost all elements of society are aware of the dangers posed from environmental damage. One of the causes of environmental damage is environmental pollution caused by the accumulation of food waste and scraps. This study is partly done by utilizing the role of citizens in reducing and utilizing the surrounding garbage. Inorganic waste originating from various household activities, such as plastic waste, cans and bottles of drinks, paper, and cloth. Inorganic waste originating from household activities with special skills can be transformed into useful items and can be of economic value, so as to increase income for the family. The problems that must be answered in this study are: how do you collect and manage inorganic waste from household activities? How do you provide knowledge to the community to minimize inorganic waste by making use of it into handicrafts of economic value? The method of activities carried out is to conduct training activities to the community especially to mothers and young women at the location of the activity, namely in the Lakkang Island tourist village, Makassar City. The training material includes introduction to household inorganic waste, giving an overview of the design of processing and utilization into handicrafts of economic value. The technical management and treatment of household inorganic waste is to sort it into paper, cloth, plastic and metal waste (cans), then collect the types of waste that can be utilized as raw material for crafts. In this activity, the type of waste that is utilized is still limited to the waste of used cloth, used cardboard, and various used plastic packaging. Used cloth and cardboard are processed into party bags, various waste plastic packaging is processed into pencil cases, tissue boxes and decorative flower pots.